Apoptosis in Rat Cornea After In Vivo Exposure to Ultraviolet Radiation at 300 nm. Issue 8 (August 2015) - Kronschläger, Martin; Talebizadeh, Nooshin; Yu, Zhaohua; Meyer, Linda Maren; Löfgren, Stefan
Abstract : Purpose: Peak toxicity for in vivo ultraviolet radiation (UVR) exposure to the lens is in the 300-nm wavelength region. However, little is known about corneal cell damage at 300 nm. The purpose of the study was to determine the time evolution of apoptosis in the cornea after in vivo exposure to 300-nm UVR. Methods: Altogether, 16 Sprague Dawley rats were divided into 4 groups and unilaterally exposed to 5 kJ/m 2 UVR (λmax : 300 nm; λ0.5 : 10 nm) for 15 minutes. After a predetermined latency period of 1, 5, 24, and 120 hours, depending on the group, the animals were killed and eyes were enucleated. Eye globes were further cryosectioned in 10-μm thick midsagittal sections. For the detection of apoptosis, the TUNEL method was applied. Results: TUNEL-positive signals were observed in the superficial epithelial cells in the exposed and control eyes at all latency periods. At 5 hours, TUNEL staining was detected in the exposed corneas in epithelial cells, keratocytes, and endothelial cells with a maximum signal at 24 hours. At 120 hours, no TUNEL staining was found in endothelial cells and only occasionally in keratocytes in exposed corneas. Signs of ulceration and stromal thinning were observed at 120 hours. Conclusions: UVR in the 300-nm wavelength region induces TUNEL staining in all 3 corneal layers. TUNEL staining of all 3 corneal layers is an early postexposure event observed after a 5-hour latency period. Corneal sterile keratolysis occurs in the time window of 24 to 120 hours probably induced by neutrophils.